2007 Electrical Insulation Conference and Electrical Manufacturing Expo 2007
DOI: 10.1109/eeic.2007.4562606
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field disturbance of partial discharge activity in a cone-plane gap

Abstract: Abstl'act-This paper presents initial partial discharge results for a simple cone-plane gap geometry under applied high voltage when a DC magnetic field is present. Initial phase resolved «I»-q-n results show that the intluence of a DC magnetic field as low as 70mT appears to alter the distribution of the +-q-n patterns. This result is important in order to understand the physical PD degradation processes occurring in the presence of the magnetic field. The extent and nature of changes within +-q-n patterns wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…The PD intensity was amplified in the above range at magnetic field induction 80 mT, even up to 50%. In power transformers, stray leakage magnetic fields of up to 700 mT may be present 6,22 ; these could even be much higher during short-circuit currents, which would lead to winding deformations 23 . The effects of a magnetic field that is created by a load current on the partial discharge parameters in power cables and on the breakdown characteristics of impregnated paper insulation were shown in 24 .…”
Section: Effect Of Magnetic Field In Insulation Systems Of Power Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PD intensity was amplified in the above range at magnetic field induction 80 mT, even up to 50%. In power transformers, stray leakage magnetic fields of up to 700 mT may be present 6,22 ; these could even be much higher during short-circuit currents, which would lead to winding deformations 23 . The effects of a magnetic field that is created by a load current on the partial discharge parameters in power cables and on the breakdown characteristics of impregnated paper insulation were shown in 24 .…”
Section: Effect Of Magnetic Field In Insulation Systems Of Power Devicesmentioning
confidence: 99%
“…It was found that the corona onset voltage and the breakdown voltage decreased with increasing the crossed magnetic field. The influence of a DC magnetic field on PD phase-resolved patterns in a corona cone-plane configuration was discussed in 6 . It has been shown that the magnitude and phase distributions of partial discharge patterns are affected by a perpendicular magnetic field.…”
mentioning
confidence: 99%
“…In 1997, Moon et al [5] studied the effect on corona discharge, showing an increased ozone production rate. In 2007, Hepburn et al [6] were the first to study the effect on PD, showing a variation in the phase resolved pattern for a point plane configuration. This investigation centers on the effect of magnetic fields on the vegetable oil applied in power transformer.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of thermal ageing on corona discharge activity in mineral oil and natural ester under different voltage profiles were studied [11]. Apart from the local electric field, the magnetic field within the transformers can also influence the partial discharge (PD) activity [12][13][14]. However, in literature, a study of magnetic field influence on PD characteristics variation is limited.…”
Section: Introductionmentioning
confidence: 99%